Caracterização do risco de hematomas em carcaças bovinas - Pellecchia, Arquimedes José Riobueno [UNESP] (2014)
Bruises on beef cattle carcasses are common worldwide causing important economic losses throughout the beef chain. The aim of this study was to characterize bruises occurrences on cattle carcasses, describing the number, location and time of occurrence, considering the animal categories and the distance from the farms to the slaughterhouse as underlying factors. The study was carried out in a commercial slaughterhouse located at São Paulo state (Brazil), with a daily slaughter capacity of 800 animals, assessing 22,324 carcasses. The bruises were characterized according to the area of occurrence in the carcass (forequarter, loin, ribs and hindquarter) and color, classifying as new (those with bright red coloring) and old (those with brown or yellow coloring). The numbers of bruises per carcass (total, new and old) were analyzed using generalized linear models, applying the GLIMMIX procedure of SAS statistical software and assuming the Poisson distribution for all dependent variables. The post hoc Tukey test was performed for comparison of means. To assess the risk of bruising on carcasses, a model of logistic regression was used with the application of SAS GENMOD procedure, considering as dependent the following variables: occurrence of total number of bruises (TNB), recent bruises (RB), old bruises (OB), bruises on the forequarter (BF), bruises on the loin (BL), bruises on the ribs (BR), and bruises on the hindquarter (BR). The percentages of carcasses with bruises were high for all animal categories, ranging from 62.24% for no castrated males to 83.8%, for cows. The most frequent bruises were those located on the ribs (49.02% of carcasses) and on the hindquarter (36.15%), when compared with the bruises observed on the forequarter (23.82%) and loin (14 59%). The greatest risk of ...